Centrosomes: Til O-GlcNAc Do Us Apart - Yuan, Aiyun; Tang, Xiangyan; Li, Jing (Frontiers in Endocrinology, 2021)
The centrosome apparatus is vital for spindle assembly and chromosome segregation during mitotic divisions. Its replication, disjunction and separation have to be fine-tuned in space and time. A multitude of post-translational modifications (PTMs) have been implicated in centrosome modulation, including phosphorylation, ubiquitination and acetylation. Among them is the emerging O-linked N-acetylglucosamine (O-GlcNAc) modification. This quintessential PTM has a sole writer, O-GlcNAc transferase (OGT), and the only eraser, O-GlcNAcase (OGA). O-GlcNAc couples glucose metabolism with signal transduction and forms a yin-yang relationship with phosphorylation. Evidence from proteomic studies as well as single protein investigations has pinpointed a role of O-GlcNAc in centrosome number and separation, centriole number and distribution, as well as the cilia machinery emanating from the centrosomes. Herein we review our current understanding of the sweet modification embedded in centrosome dynamics and speculate that more molecular details will be unveiled in the future.